ЗНАЧЕНИЕ ГАСТРОМУКОПРОТЕИНА В МЕТАБОЛИЗМЕ ВИТАМИНА В12. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In the article, the role and importance of gastromucoprotein in skin-genital diseases is detailed. Gastromucoprotein (Casle's intrinsic factor) is a thermolabile glycoprotein (gastromucoprotein) produced by parietal cells in the dome and body of the stomach and plays an important role in vitamin B12 metabolism.